Out-of-School Learning Environments: Expanding Classroom Boundaries and Diversifying Learning Practices - Zhou, Longjun (Science Insights Education Frontiers, 2025)
In traditional in-school learning environments, educational activities are often constrained by factors like the fixed school schedule, unchanged teaching space, and established curriculum arrangements. While the classroom serves as the primary formal learning environment for knowledge acquisition, in-class teaching alone is far from adequate for cultivating diverse competences in students, particularly practical skills, interdisciplinary ability, and social adaptability. In contrast, out-of-school learning environments (OSLEs), such as natural environments, science and cultural venues, and virtual learning platforms, have the potential to create a wider variety of learning opportunities by transcending the physical and institutional boundaries of the school.